(untitled) (Periodicals of Engineering and Natural Sciences, 2021)
In the modern construction industry, a solution being successfully proven is the use of geosynthetic materials, applied as semi-holders, to increase the reliability and stability of soil structures. In connection therewith, solving the issues of expanding the range of methods and approaches to predicting the behavior of such structures under the activity of surface loads is a relevant task, since this is a vital factor in evaluating the designing arrangements made, including the use of geosynthetic materials. The aim of the studies according to this paper is to expand the pertinence of the mechanics of granular media (MGM) in order to assess the reliability of decisions made in the design of soil structures from pitifully durable soils, supported with geosynthetic materials, by comparing the obtained values with the results of full-scale tests and the values obtained by the limited component strategy. For this purpose, the paper presents a comparative analysis for the results of determining vertical stresses under the bridge reinforced with geosynthetic materials and its displacement, obtained by the mechanics of granular media and the limited component strategy. The results of laboratory tests, performed in a soil tray, were taken as verification data. The actual values of vertical stresses were determined using soil pressure sensors, and the values of displacement were determined using the movement indicator of the clockwork installed on the deflection meter of a die unit. An approach to determining displacement of a reinforced bridge using the mechanics of granular media was presented for the first time. The newly presented approach to determining displacement of an bridge, reinforced at the base with geosynthetic materials, allows us to conclude on its reliability, which significantly expands the applicability of the MGM as an alternative to the use of the limited component strategy. The aftereffects of contrasting the upsides of vertical anxieties under the bridge reinforced with geosynthetic materials and its displacement, utilizing the Plaxis programming bundle and the MGM dependencies, counting when contrasted and the consequences of lab tests, are presented. Based on the results obtained, a general conclusion was made on the possibility to use the MGM dependencies in deciding the example of the pressure dispersion and the values of displacement of reinforced bridges under the action of surface loads. The paper also discloses the promising directions of research in this area of geotechnical engineering.